Comparative Study between Oxytocin and Carbetocin for the prevention of Primary Postpartum Hemorrhage following Caesarean Section (Ibrahim Cardiac Medical Journal, 2022)
Background & objective: Of the many pharmacological options for the management of postpartum hemorrhage, oxytocin is the first line of treatment. The newer drug carbetocin is getting popularity among obstetricians, although there is as yet not enough evidence about its safety and efficacy. The present study attempted to compare oxytocin with carbetocin for the routine prevention of postpartum hemorrhage (PPH) following caesarean section.Methods: The present comparative clinical trial was conducted in the Department of Obstetrics and Gynaecology in Rajshahi Medical College Hospital (RMCH), Rajshahi over a period of one year between March 2017 to February 2018. Pregnant women undergoing cesarean section under regional anaesthesia and do not have known hypersensitivity to oxytocin and carbetocin and known bleeding disorders were included in the study. A total of 96 such subjects were consecutively included and were randomly assigned to either Oxytocin (n = 48) and Carbetocin (n = 48) Groups. The outcome was evaluated in terms of incidence of PPH (loss of blood > 1000 ml), blood transfusion needed to compensate for lost blood, additional oxytocics needed to manage PPH and adverse effects encountered by the subjects.Result: The mean age of the subjects was around 25 years and the age distribution between the study groups was almost similar. In terms of obstetric characteristics multigravida was predominant in the Oxytocin group than that in the Carbetocin group. The current pregnancy profile like gestational age, ANC received, number of foetus in utero and placental position all were comparable between the groups. Antenatal conditions/diseases deemed to have influence on PPH were no different between the study groups. Past history of caesarean section was higher in Oxytocin group (43.8%) than that in the Carbetocin group (22.9%). There were negligible incidences of past PPH and myomectomy in either group. The mean haemoglobin level in the former and the latter groups were 9.5 and 10 gm/dl respectively with majority of the subjects being mildly anaemic. More than 80% of the subjects in either group underwent emergency caesarean section. The outcome showed that 83% in the Oxytocin group and 90% in the Carbetocin group did not develop PPH, but the difference was not significant. The mean blood lost was somewhat lower in the carbetocin group (630 ml) than that in the Oxytocin group (685 ml). The number of patients needed to be transfused and the mean amount of blood transfused to them in each group was fairly comparable. Oxytocin group received additional oxytocic drugs, such as, Metherspan and Misoprostol more frequently than the Carbetocin group did, but the differences did not turn significant. A few patients in both groups developed adverse effects but they were comparable. The mean 24-hours urine output was > 2000 ml in either group).Conclusion: The study concluded that the incidence of PPH, the amount of blood lost, number of patients transfused, amount of blood transfused and the additional amount of oxytocics required for the prevention and treatment of PPH were broadly comparable between the two study groups.Ibrahim Card Med J 2021; 11 (1): 71-78